Non-Uniform Metasurface-Integrated Circularly Polarized End-Fire Dipole Array Antenna - Nkimbeng, Cho Hilary Scott; Wang, Heesu; Byun, Gangil; Park, Yong Bae; Park, Ikmo (Journal of Electromagnetic Engineering and Science, 2023)
This paper presents a high-gain wideband circularly polarized antenna composed of an end-fire dipole array antenna integrated with a metasurface. The antenna consists of a two-layer cascaded non-uniform metasurface made up of 4 × 4 circular patches with cross-slots of unequal lengths placed above an end-fire dipole array antenna with an air gap between the structures. The end-fire dipole array antenna comprises four equally spaced dipole elements, and each dipole is connected to a parallel stripline printed on the front and back sides of the substrate. The metasurface, which is made up of a circular patch with 2 × 2 center patches that have a different radius than the outer patches, and the cross-slots of unequal lengths are used for the polarization conversion of a linearly polarized wave to a circularly polarized wave. The measured reflection coefficients for |S11| < -10 dB yielded an impedance bandwidth of 25.6–31.8 GHz (21.5%), a 3-dB axial ratio (AR) bandwidth of 26.1–30.5 GHz (15.5%), a 3-dB gain bandwidth of 26.0–31.1 GHz (17.4%) with a peak gain of 11.0 dBic, and a radiation efficiency of more than 80% in the axial ratio bandwidth.
Keywords: Circular Polarization; End-Fire Array Antenna; Metasurface; Polarization Conversion Surface; Printed Dipole Array Antenna